Mechanical circulatory support as bridge therapy for heart transplant: case series report - Javier D. Garzon-Rodriguez; Carlos Obando-Lopez; Manuel Giraldo-Grueso; Nestor Sandoval-Reyes; Jaime Camacho; Juan P. Umaña (BMC Research Notes, 2018)
Abstract Background Mechanical circulatory support (MCS) represents an effective urgent therapy for patients with cardiac arrest or end-stage cardiac failure. However, its use in developing countries as a bridge therapy remains controversial due to costs and limited duration. This study presents five patients who underwent MSC as bridge therapy for heart transplantation in a developing country. Case presentation We present five patients who underwent MCS as bridge therapy for heart transplant between 2010 and 2015 at Fundación Cardioinfantil-Instituto de Cardiología. Four were male, median age was 36 (23–50) years. One patient had an ischemic cardiomyopathy, one a lymphocytic myocarditis, two had electrical storms (recurrent ventricular tachycardia) and one an ischemic cardiomyopathy with an electrical storm. Extracorporeal life support (ECLS) was used in three patients, left ventricular assistance in one, and double ventricular assistance in one (Levitronix® Centrimag®). Median assistance time was 8 (2.5–13) days. Due to the inability of cardiopulmonary bypass weaning, two patients required ECLS after transplant. One patient died in the intensive care unit due to type I graft rejection. Endpoints assessed were 30-day mortality, duration of bridge therapy and complications related to MCS. Patients that died on ECLS, or were successfully weaned off ECLS were not included in this study. Conclusions MCS is often the only option of support for critically ill patients waiting for a heart transplant and could be considered as a short-term bridge therapy.